Isolation to Interface to Integration - Roberts, J. M.; Eng, C. (Methods of Information in Medicine, 2006)
Objectives: Over thirty years both divergence and synergy have been seen in the health informatics (HI) domain; to the point where aspiration is towards a collective environment recognising HI as a mature discipline internationally. The author considers catalysts and inhibitors to this goal over 30 years, and asks the question – is one professional identity achievable and desirable?This review of development of HI aims to promote reflection of the status, value and attributable influence with a view to recognising an internationally entity. Aspects of professionalism, practice, regulation and registration can then be refined to produce a universally understood inclusive community without loss of distinction to sub-specialties within it.Methods: The author utilised literature searches, research studies, domain knowledge and cooperative inquiries as context. Evaluation of issues is grounded in learned society investigations of professionalism and commitment to development of professional registration of those in informatics for the care domain.Results: Transition from isolated applications through interfaced ‘best of breed’ solutions working together to integrated closely coupled single-vendor solutions is mirrored by professional groups, established through special interests, working together on big initiatives and then formally benefiting from a cohesive group. Phasing of such staged development is different by country or by focus/topic.Conclusions: The global HI situation will never again be as diverse as historically it was. Recognition of the lifecycle of the interacting factors explored in this paper will help HI to assume a world-wide brand identity whilst sustaining the subsidiarity of specialist cohorts within it.
Keywords: Health informatics; fragmentation; history; organisation; maturity